Identification of schizophrenic patients by examination of body odor using gas chromatography-mass spectrometry and a cross-selective gas sensor array - Di Natale, Corrado; Paolesse, Roberto; D'Arcangelo, Giuseppe; Comandini, Paolo; Pennazza, Giorgio; Martinelli, Eugenio; Rullo, Santo; Roscioni, Maria Claudia; Roscioni, Claudio; Finazzi-Agrò, Alessandro; D'Amico, Arnaldo (Medical science monitor, 2005)
Previous findings have shown that the body odor of patients affected by schizophrenia contains some specific compounds. Chemical sensor technology has proved to be able to classify different odours. We investigated the possibility of using a chemical sensor array to detect body odor alteration in schizophrenic patients. The sweat of subjects was sampled and analysed by Gas Chromatography-Mass Spectrometry (GC-MS) and by an array of cross-selective gas sensors. A total of 27 individuals were involved in the experiment: 9 schizophrenics, 9 with other mental disorders, and 9 controls. GC-MS analysis showed a richer composition for the sweat of schizophrenic patients. Nevertheless, the individuation of specific markers was unsuccessful. On the other hand, statistical analysis of cross-selective gas sensor data provided a complete classification of schizophrenic patients with respect to the other three groups. The alteration of body odor in schizophrenic patients was confirmed by GC-MS and chemical sensor array. Results show that the alteration is complex and cannot be limited to a single compound, but rather to a global variation of the body odor.